Typification of Dioscorea communis and its synonym Tamus communis var. subtriloba (Dioscoreaceae) - Ferrer-Gallego, Pedro Pablo; Boisset, Fernando (Phytotaxa, 2016)
The typification of Dioscorea communis (≡ Tamus communis, Dioscoreaceae) is discussed. The designation of the nomenclatural type is based on the consultation of Linnaeus’s original material preserved at LINN, the Clifford Herbarium at BM, the Herbarium Joachim Burser at UPS, and the literature cited in the protologue. The name is lectotypified using a herbarium sheet preserved at LINN. A lectotype is also selected for the name Tamus communis var. subtriloba, from a specimen preserved at the Gussone’s herbarium at NAP.